The Effect Of Deletion and Mention on Esthetics of The style (Journal of Hama University, 2019)
The sentence in Arabic is compounds of underpinned and was undereinned on it and some of belongings, some of them come mentioned and some deleted. No doubt that every deletion or mention has an effect on the Asthetic of the style, this our research is trying to concentrate on the two style of deletion and mentioning, and clearifying the asthetic effect of using them, The pronunciation may come mentioned in position and deleted in another one. And the speech may come completed with all its elements, and an element maybe deleted of it, and all that is setted in the organizing theory which it is careful about syntax grammars, and considering what situation wants. Deletion position is not mention position, and every one of them has its own rhetorical connotations and mysteries which meaning denotes and context needs, and the purpose which it seeks to achieve.